Challenges and Approaches to Crop Improvement Through C3-to-C4 Engineering - Cui, Hongchang (Frontiers in Plant Science, 2021)
With a rapidly growing world population and dwindling natural resources, we are now facing the enormous challenge of increasing crop yields while simultaneously improving the efficiency of resource utilization. Introduction of C4 photosynthesis into C3 crops is widely accepted as a key strategy to meet this challenge, because C4 plants are more efficient than C3 plants in photosynthesis and resource usage, particularly in hot climates, where the potential for productivity is high. Lending support to the feasibility of this C3-to-C4 engineering, evidence indicates that C4 photosynthesis has evolved from C3 photosynthesis in multiple lineages. Nevertheless, C3-to-C4 engineering is not an easy task, as several features essential to C4 photosynthesis must be introduced into C3 plants. One such feature is the spatial separation of the two phases of photosynthesis (CO2 fixation and carbohydrate synthesis) into the mesophyll and bundle sheath cells, respectively. Another feature is the Kranz anatomy, characterized by a close association between the mesophyll and BS cells (1:1 ratio). These anatomical features, along with a C4-specific carbon fixation enzyme (PEPC), form a CO2-concentration mechanism that ensures a high photosynthetic efficiency. Much effort has been taken in the past to introduce the C4 mechanism into C3 plants, but none of these attempts has meet with success, which is in my opinion due to a lack of system-level understanding and manipulation of the C3 and C4 pathways. As a prerequisite for the C3-to-C4 engineering, I propose that not only the mechanisms that control the Kranz anatomy and cell-type specific expression in C3 and C4 plants must be elucidated, a good understanding of the gene regulatory network underlying C3 and C4 photosynthesis must also be achieved. In this review, first I describe past and current efforts to increase photosynthetic efficiency in C3 plants and their limitations. Then I discuss a systems approach to this challenge, some practical issues, and recent technical innovations that would help us to solve these problems.